Ice action on Nanisivik Wharf, Winter 1979-1980 - Frederking, R. M. W.; Nakawo, M. (1984)
During the period December 1979 to June 1980, five visits were made to observe and measure ice behaviour around the wharf at Nanisivik, on Baffin Island. The measurements included ice thickness, temperature, salinity, and density, as well as horizontal movements of the ice cover. In March 1980, additional measurements and observations were made of tides, rotations of the ice sheet, and grain structure of the ice. A model for the formation of an active zone of ice between the wharf and the adjacent ice cover has been proposed, based on the observed evolution of ice conditions and internal structure of the active zone. Horizontal growth of the active zone displaces the adjacent ice cover away from the wharf, and in so doing, generates ice pressure estimated at 69 kPa on the wharf. Entre décembre 1979 et juin 1980 on a effectué cinq visites au quai de Nanisivik sur l'île de Baffin afin d'y observer le comportement de la glace et d'en mesurer les déplacements. On a mesuré l'épaisseur, la temperature, la salinité et la densité de la glace ainsi que les déplacements horizontaux de la couverture de glace. En mars 1980 on a effectué de nouvelles mesures et observations des marées, des rotations de la couche de glace et de la structure granulaire de la glace. On a proposé un modèle de la formation d'une zone active entre le quai et la glace adjacente basé sur l'evolution observée des conditions de glace et de la structure interne de la zone active. L'agrandissement dans le plan horizontal de la zone active é loigne du quai la couverture de glace adjacente et engendre ainsi des charges estimées à 69 kPa sur le quai. Peer reviewed: Yes NRC publication: Yes